Effect of octreotide on gall stone prevalence and gall bladder motility in acromegaly. Issue 2 (February 1993) - Catnach, S M; Anderson, J V; Fairclough, P D; Trembath, R C; Wilson, P A; Parker, E; Besser, G M; Wass, J A
Abstract : Octreotide therapy in acromegaly is associated with an increased prevalence of gall stones, which may be the result of an inhibition of gall bladder motility. Gall stone prevalence in untreated acromegalic patients relative to the general population is unknown, however, and the presence of gall stones and gall bladder motility in these patients and in acromegalic patients receiving octreotide was therefore examined. Thirty four percent of 39 patients who had taken octreotide for a mean of 20 months had gall stones compared with 16% of 38 patients who had not been treated with octreotide (p < 0.005). In a subgroup of 21 patients studied prospectively over 4 to 18 months, two patients developed stones. No patient had symptoms referrable to their gall stones. In 31 untreated acromegalic patients, the mean fasting gall bladder volume was similar to that in normal subjects. Maximal percentage emptying, however, was impaired (34 v 64%, p < 0.001) and the mean postprandial residual gall bladder volume increased (21.7 v 9.0 ml, p < 0.001). Treatment with octreotide increased the mean postprandial residual volume further to 36.8 ml (p < 0.001). Gall bladder emptying in untreated acromegalic subjects is impaired. Octreotide further increases postprandial residual gall bladder volume and this may be a factor in the increased gall stone prevalence seen in these patients.